Llama rocks the cradle of chaos - Stutzman, Jonathan; Fox, Heather (New York : Henry Holt Books for Young Readers, 2022)
Greedy Llama travels back in time to eat his marvelous birthday donut a second time, but a Baby Llama follows him to the present, and soon his house is a chaos of cave llamas, barbarian bunnies, and Viking pigs.
Ages 4-8.
Grades 2-3.
Keywords: Llamas -- Juvenile fiction; Time travel -- Juvenile fiction; Humorous stories; Llamas -- Fiction; Time travel -- Fiction; Humorous fiction